A mechanistic framework for auxin dependent Arabidopsis root hair elongation to low external phosphate - Bhosale, Rahul; Giri, Jitender; Pandey, Bipin K.; Giehl, Ricardo F.H.; Hartmann, Anja; Traini, Richard; Truskina, Jekaterina; Leftley, Nicola; Hanlon, Meredith; Swarup, Kamal; Rashed, Afaf; Voß, Ute; et al. (Nature Publishing Group, 2018)
Phosphate (P) is an essential macronutrient for plant growth. Roots employ adaptive mechanisms to forage for P in soil. Root hair elongation is particularly important since P is immobile. Here we report that auxin plays a critical role promoting root hair growth in Arabidopsis in response to low external P. Mutants disrupting auxin synthesis (taa1) and transport (aux1) attenuate the low P root hair response. Conversely, targeting AUX1 expression in lateral root cap and epidermal cells rescues this low P response in aux1. Hence auxin transport from the root apex to differentiation zone promotes auxin-dependent hair response to low P. Low external P results in induction of root hair expressed auxin-inducible transcription factors ARF19, RSL2, and RSL4. Mutants lacking these genes disrupt the low P root hair response. We conclude auxin synthesis, transport and response pathway components play critical roles regulating this low P root adaptive response.